ANALISA PENGARUH LABA BERSIH DAN ARUS KAS TERHADAP RETURN SAHAM PADA PERUSAHAAN FOOD AND BEVERAGES: STUDI EMPIRIS DI BURSA EFEK INDONESIA - Haryatih, Haryatih Haryatih (Jurnal Riset Keuangan dan Akuntansi, 2016)
Target of this research to test influence of net income and cash flow to stock returns of at Food and Bevarages Companys: empirical study in effect exchange Indonesia. Variable used by as much 5 consisted of by 4 independent variable and 1 variable dependen. 4 independent variable that is net income, cash flow operate for, cash flow investment, and the cash flow financing. While 1 variable of dependen that is stock returns.This research test 10 Food and Bevarages Companys which have been enlisted in effect echange of Indonesia and have published financial statement which have been made an audit of by 31 December 2012 – 2015 representing the part of consideration of at determination of sampel by using purposive sampling. Statistical methods used by is doubled linear regression by using tes-t and tes F of at storey level of signifikansi 5%.Result of research individually prove that net income and cash flow operating have an effect to return share. While together is net income, cash flow operate for, cash flow investment, and cash flow of financing have an effect on positive to stock returns. This matter show indication that stock returns of influenced by Food and Beverage Company emiten of existence of publicing it the financial statement specially which deal with information of performance of company of found on income statement and cash flow statement.